Waiting and Disenchantment: Kourouma’s ’Les Soleils des Indépendances’ and Oupoch’s ’En attendant la Liberté’ - Uwah, Godwin Okebaram (Afrika Focus, 1987)
Like Samuel Beckett’s characters in En attendant Godot, the protagonists of Ahmadou Kourouma’s Les Soleils des Indépendances and Gnaoulé Oupoh’s En Attendant la Liberté wait for something to happen to change their lives. As they wait, they ascribe to the object of waiting an absolute certainty translated in terms of recognition, realization of the promises of independence, continuity of dynasty, freedom, and other good life-values. Ultimately, disenchantment displaces hope; the object of waiting eludes them and their general condition either worsens or, at best, remains static. Paradoxically, the characters continue to wait in anticipation of a turn-around in their destiny. Waiting thus becomes a type of imprisonment. To break the impasse, Oupoh seems to advocate continued struggle and a timely confrontation to effect change. Kourouma, on the other hand, appears to endorse existential revolt and self-abnegation; in his estimation, any change that does not liberate man from his Self merely perpetuates self-imprisonment. But for both the waiting game continues, and so does the paradox. KEYWORDS : West Africa, Kourouma, literature, motives, Oupoh